Prevalences of mental health disorders among low- and lower middle-income countries' children and adolescents exposed to extreme weather events: a systematic review and meta-analysis - Choi, Munkyung Elizabeth (Department of Public Health and Family Medicine, 2025)
Background: Research concerning the disproportionate health consequences of climate change is still unexplored, specifically in one of the most vulnerable populations: children and adolescents living in low- and lower middle-income countries (LLMICs). At present, there is a gap in current literature on how prevalent LLMIC youth mental health burdens are following climate-induced extreme weather events (EWEs). This systematic review serves to uncover these mental health burdens in response to the EWEs projected to intensify in the near future. Methods: The Context Condition Population (CoCoPop) framework for prevalence studies was used to identify eligible studies. Mental health disorders were the condition of interest, in the context of LLMICs under the population of children and adolescents (1 to 19 years of age) who had experienced at least one EWE. MEDLINE via PubMed, PsychINFO, Web of Science Core Collection, Scopus, and CINAHL were databases retrieved using the search strategy. All searches were done in June 2024. Two researchers screened and three extracted the data. Meta-analyses were conducted using R (4.2.3). Results: Twenty-seven studies met the eligibility criteria with a total sample population of 14239 participants. The most prevalently reported mental health disorders identified were anxiety (32.7% 95% CI: 7.1-65.6), depression (33.2% 95% CI: 17.0-51.8), and post-traumatic stress disorder (PTSD) (50.4% 95% CI: 36.7-64.1). Heterogeneity as high in all groups (I² = >90%). Subgroup analyses were conducted, grouped by type of EWE, age, region, time-point measured, and measurement tool standardization. Conclusions: This review provides critical insights into the mental health burdens LLMIC youth face after experiencing EWEs. Anxiety, depression, and PTSD are commonly found prevalent, influenced by factors such as the type of EWE, age, region, different time points measured, and measurement tools' standardization. The high heterogeneity observed across studies highlights the challenges in standardizing mental health measurements, especially in LLMIC settings. Influential factors must be considered to fully comprehend and address the complexities of the vulnerable group's mental health states. LLMIC stakeholders must not only acknowledge mental health disorder repercussions from EWE exposures but also translate such evidence into palpable interventions.